2021
DOI: 10.1073/pnas.2016107118
|View full text |Cite
|
Sign up to set email alerts
|

On explosive boiling of a multicomponent Leidenfrost drop

Abstract: The gasification of multicomponent fuel drops is relevant in various energy-related technologies. An interesting phenomenon associated with this process is the self-induced explosion of the drop, producing a multitude of smaller secondary droplets, which promotes overall fuel atomization and, consequently, improves the combustion efficiency and reduces emissions of liquid-fueled engines. Here, we study a unique explosive gasification process of a tricomponent droplet consisting of water, ethanol, and oil (“ouz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…More importantly, the Leidenfrost effect holds promising keys to many important industrial applications. For instance, engineering the hydrophobicity, roughness, and wettability of solid surfaces via structural microtexturing allowed for tuning the Leidenfrost point by hundreds of degrees, with implications for cooling and thermal management in steel and aerospace industry, combustion, and nuclear plants . Rational fabrication of asymmetrical surface microstructures was proven an efficient way to design micromotors and actuators by harvesting the energy produced in the frictionless movements of objects. , The temperature gradient and the corresponding charge separation have been utilized in the chemical synthesis of functional nanomaterials. , In addition to the original Leidenfrost effect, where the vapor cushion was produced from the evaporation of liquid droplets, multiple variations have been proposed to expand the mechanisms for generating the vapor cushion, including the evaporation of hydrogels, the sublimation of solid objects like dry ice, and the evaporation or sublimation of the cold surface (like liquid nitrogen or dry ice) when interacting with room temperature objects. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, the Leidenfrost effect holds promising keys to many important industrial applications. For instance, engineering the hydrophobicity, roughness, and wettability of solid surfaces via structural microtexturing allowed for tuning the Leidenfrost point by hundreds of degrees, with implications for cooling and thermal management in steel and aerospace industry, combustion, and nuclear plants . Rational fabrication of asymmetrical surface microstructures was proven an efficient way to design micromotors and actuators by harvesting the energy produced in the frictionless movements of objects. , The temperature gradient and the corresponding charge separation have been utilized in the chemical synthesis of functional nanomaterials. , In addition to the original Leidenfrost effect, where the vapor cushion was produced from the evaporation of liquid droplets, multiple variations have been proposed to expand the mechanisms for generating the vapor cushion, including the evaporation of hydrogels, the sublimation of solid objects like dry ice, and the evaporation or sublimation of the cold surface (like liquid nitrogen or dry ice) when interacting with room temperature objects. , …”
Section: Introductionmentioning
confidence: 99%
“…For instance, engineering the hydrophobicity, roughness, and wettability of solid surfaces via structural microtexturing allowed for tuning the Leidenfrost point by hundreds of degrees, 11 with implications for cooling and thermal management in steel and aerospace industry, combustion, and nuclear plants. 12 Rational fabrication of asymmetrical surface microstructures was proven an efficient way to design micromotors and actuators by harvesting the energy produced in the frictionless movements of objects. 3,13 The temperature gradient and the corresponding charge separation have been utilized in the chemical synthesis of functional nanomaterials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In some cases, the presence of an additional phase in a liquid drop can lead to a significant change in the drop outcome. For example, 31,32 the presence of small impurities or gasification of the liquid can lead to micro explosions in the drop during its spreading on a hot substrate. However, the mechanisms of boiling in a suspension drop are completely different.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the potential of this emulsified feedstock technique in chemical production. [8][9][10][11] Due to the great potential of micro-explosion application, a large number of researchers have sought to understand its mechanism and regular patterns by exploring and observing the micro-explosion phenomenon of single droplets [12][13][14] . It has been found that there are at least two different forms of micro-explosion in single droplet micro-explosion experiments, namely "micro-explosion" and "puff" 12,[15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%